1994
DOI: 10.1161/01.atv.14.8.1290
|View full text |Cite
|
Sign up to set email alerts
|

Early changes of the arterial carotid wall in uncomplicated primary hypertensive patients. Study by ultrasound high-resolution B-mode imaging.

Abstract: Arterial hypertension is frequently responsible for arteriosclerotic damage in the carotid region. Nevertheless, there is as yet no general agreement that hypertension is correlated with lesions detected by noninvasive means in the carotid arteries. We studied, by noninvasive echotomographic technique, 70 uncomplicated primary hypertensive individuals without clinically evident end-organ complications and 30 normotensive matched control subjects to detect early lesions of carotid arteries. The presence of othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0
2

Year Published

1998
1998
2007
2007

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 44 publications
4
18
0
2
Order By: Relevance
“…30 To this purpose, it is useful to remember that BP and serum cholesterol levels are positively correlated with IMT in several studies. 17,35,36 This finding is also in agreement with the results of another study 37 which demonstrated in Chinese patients the role of hypertension, hypercholesterolaemia, and hypertrygliceridaemia in the pathogenesis of carotid atherosclerosis.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…30 To this purpose, it is useful to remember that BP and serum cholesterol levels are positively correlated with IMT in several studies. 17,35,36 This finding is also in agreement with the results of another study 37 which demonstrated in Chinese patients the role of hypertension, hypercholesterolaemia, and hypertrygliceridaemia in the pathogenesis of carotid atherosclerosis.…”
Section: Discussionsupporting
confidence: 88%
“…17 More recently 38 other authors stated that the relationship of BP variability with LV hypertrophy or carotid damage is controversial and this finding may further support the lack of correlation between ventricular hypertrophy and carotid damage.…”
Section: Discussionmentioning
confidence: 87%
“…11,12 This technique allows a high reproducibility of the measurements, as already shown in a previous study. 23 Peripheral artery assessment of significant atherosclerosis The resting ankle-brachial pressure index (ABPI) was measured with the subject in supine position with an 8-MHz continuous-wave Doppler probe. The value of the highest systolic blood pressure measured at the ankle was divided to the highest blood pressure measured in both arms.…”
Section: Pulsed Doppler Echocardiographymentioning
confidence: 99%
“…A previous report shows side-related differences in intima-media thickness of carotid arteries in primary hypertensive patients. 2 To evaluate the possibility of side-related influences on the relationship between overweight or obesity and carotid intima-media thickness, we performed a separate analysis for the right and left common carotid artery in our cohort of free-living middle-aged women. No side-related differences were detected in the mean values of common carotid intima-media thickness (right common carotid artery, 0.98Ϯ0.01; left common carotid artery, 0.97Ϯ0.01 [meanϮSE]).…”
Section: Responsementioning
confidence: 99%